KELAYAKAN LEAFLET MATERI KEANEKARAGAMAN HAYATI DARI BUAH DADAMUK, KARIAMPUK DAN MENJALIN DI KABUPATEN BENGKAYANG - Meldasari, Meldasari; Daningsih, Entin; Titin, Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to determine the feasibility of leaflet media on biodiversity material in class X SMA from the result of morphology, nutrient content and fruit fiber of dadamuk (Microcos latifolia Burret), kariampuk (Sandoricum borneense Miq.) and menjalin (Salacia fruticosa Wall.). This research was descriptive method using purposive sampling technique. Made leaflet followed by validation carried out inÂ two stages, namely instrument validation and media with three aspects (content, language and construction). Consisting and criteria leaflet validated by five validators,two lecturers of Biology Education FKIP Tanjungpura University and three Biology teachers one subject in Pontianak City and two in Bengkayang District. Data a validation was analyzed using of Content Validity Ratio (CVR) and Content Validity Index (CVI) formulas. Leaflet validation result obtained the value of CVR and CVI was achieved a value of 0.95. Therefore the leaflet was valid and feasible to used as a learning media on biodiversity material in high school.Keywords: Leaflet, Biodiversity, Dadamuk, Kariampuk, Menjalin.